The undeclared war that dictated a new canon in Mexican poetry - Anchía Vindas, Alexander (2025)
The present article suggests that contemporary Mexican poetry, starting in the 20th century, was founded by means of two great creative forces, as conceived by Friedrich Nietzsche in his work The Origin of Tragedy. Although it is a subjectivist view that prevails in this analysis, it is focused on some clues and on the author’s own analysis as a suggestion. While Jaime Sabines, a poet from the south of Mexico, could be near the Dionysian trend; Octavio Paz, meanwhile, approaches more to the Apollonian way. Both poets shared a creative life during about fifty years. Although the labels that associate Sabines with one force or identify Octavio Paz with the other force established by Nietzsche, both are referents for Mexican poets of the twentieth and twenty-first centuries.